2018
DOI: 10.17557/tjfc.421974
|View full text |Cite
|
Sign up to set email alerts
|

FEED VALUE OF MAIZE (Zea mays var. indentata (Sturtev.) L.H.Bailey) GRAIN UNDER DIFFERENT IRRIGATION LEVELS AND NITROGEN DOSES

Abstract: The aim of the study was to investigate effects of different irrigation levels and nitrogen doses to chemical composition, in vitro gas and methane production of maize kernel for animal feeding. Three different nitrogen doses such as 100, 200 and 300 kg ha-1 N and irrigation levels such as 50%, 75% and 100% of depleted water were applied. The study was carried out under split plot for randomized complete block experimental design with three replicates during 2013-2014 seasons and irrigation levels were allocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…Similar findings were also reported by [Nawaz et al,] that exogenous application of Se significantly improved the fodder yield and quality in maize under water deficit conditions [28], which were found very close to the present results. The results of the present study were further supported with the reports of [Kale et al,] that different nitrogen doses significantly reduced the ADF concentration in maize under irrigation stressed conditions [23].…”
Section: Acid Detergent Fiber (%) (Adf) Of Maize Fodder Silagesupporting
confidence: 92%
See 3 more Smart Citations
“…Similar findings were also reported by [Nawaz et al,] that exogenous application of Se significantly improved the fodder yield and quality in maize under water deficit conditions [28], which were found very close to the present results. The results of the present study were further supported with the reports of [Kale et al,] that different nitrogen doses significantly reduced the ADF concentration in maize under irrigation stressed conditions [23].…”
Section: Acid Detergent Fiber (%) (Adf) Of Maize Fodder Silagesupporting
confidence: 92%
“…Therefore, fodder with higher ash contents should be avoided. In an experiment conducted by Kale et al (2014) it was concluded that water stress along with higher doses of nitrogen significantly increased the crude ash contents in maize [ 23]. In our findings the decreased contents of ash with the foliar application of GA3 and Se might be due to their more enzymatic activity promoting function under drought stress than enhancing the mineral uptake.…”
Section: Ash Contents (%) Of Maize Fodder Silagesupporting
confidence: 59%
See 2 more Smart Citations